Analisis Kointegrasi Arus Kunjungan Wisatawan Dari Australia dan Malaysia Ke Indonesia - Sarwoko Sarwoko (EBBANK, 2010)
This paper describes the using of cointegration and ecm to see the long run relationship between determinant factors and tourists arrival (as an indication of tourism demand) from Australia and Malaysia. The tourism demand factors: Gdp per capita from origin countries, Exchange rate and Tourism price are hipothezed influencing tourists arrival from those contries. Annual data from 1985 to 2007 are used for analysis. Augmented Dikey-Fuller, Phillip Peron and Johansen’s maximum likelihood tests are used to test for unit root and cointegration. An error correction model (ECM) are estimated to an explain Australia and Malaysia demand for tourism to Indonesia. The results show that  the long run equilibrium exists among endogen variables and  their tourist seem to be highly sensitive to the per capita real income and exchange rate variables.